The Impact of Training Program on Employee Career Development in Pullman Ciawi Vimala Hills Hotel - Eviana Tarigan; Liliana Dewi (Budapest International Research and Critics University, 2022)
This research aims to analyze the impact of training Program towards employee career development in Pullman Ciawi Vimala Hills Hotel. The study source used primary data in the form of questionnaire and given to 52 respondents. The results of this study are training program influential significantly for the career development of employees in hotel Pullman Ciawi Vimala Hills.